ANALISIS PENGENDALIAN MANAJEMEN KUALITAS PRODUKSI DENGAN METODE STATISTICAL PROCESS CONTROL (SPC) UNTUK MEMINIMALKAN PRODUK CACAT PADA KONVEKSI BASIR KLATEN - Prasetyo, Jarot; Santoso, Imam; Hastuti, Nur Windhi (FAKULTAS EKONOMI DAN PSIKOLOGI UNWIDHA KLATEN, 2024)
Basir Konveksi is a home-based convection business in Buntalan Village, Klaten Regency. The products produced are kindergarten, elementary and middle school uniforms, kindergarten drumbands, sports t-shirts, graduation uniforms, sinoman uniforms, school vests. This convection has problems, namely the accumulation of semi-finished and finished materials in the warehouse due to the unsupervised fabric cutting process. This research aims to find out how to minimize defective products using the Statistical Process Control (SPC) method. Observing one of the production flows, namely the production of kindergarten uniforms, obtained variable data consisting of four types, namely shirt length, shirt sleeve length, trouser length and waist circumference. Attribute data in the form of dirty materials or fabric, pieces of fabric that exceed or fall below the standard and attributes that have not been installed (buttons, logos, brands). The most dominant defect data discovery was fabric cuts that were more than or less than the standard, is 35.55%. Then the causes of product defects were analyzed using a fishbone diagram and it was found that the main factors causing product defects were material, machine, human, method, supervision and work environment factors. From this research, several suggestions were obtained for companies to make the right decisions in minimizing defective products and repairing them so as to obtain optimal product quality and always evaluating and improving employee performance so that employees are more disciplined and productive at work.